Pengaruh Intensitas Dzikir Hati dan Pasrah dalam Pengajian Noto Ati Malam Reboan Terhadap Kesejahteraan Sosial Ekonomi Jama’ah Pengajian Baitul Ma’ruf Cabang Lamongan - Nur Kholis Majid (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Religious moderation education has an important role in creating tolerance and social harmony in diverse societies. Religious moderation teaches a deep and balanced understanding of religious teachings, as well as their daily application without extreme or fanatical attitudes. Through this education, individuals are taught to respect differences, understand ethnic and cultural diversity, and develop mutual respect between followers of different religions. This education also emphasizes the importance of interfaith dialogue as a way to overcome conflict and build harmonious cooperation. This research aims to identify the form of religious moderation education implemented at SDN 1 Balun Turi Lamongan in building tolerance and social harmony, as well as to evaluate its impact on the formation of religious tolerance among students. The research method used is a qualitative approach, with data collection techniques through interviews, observation and documentation. Data analysis includes collection, reduction, data presentation, and drawing conclusions. The research results show that religious moderation education at SDN 1 Balun integrates moderation values ​​in every lesson and provides examples and moral messages about the importance of tolerance and social harmony. This implementation has a positive impact, reducing conflict between religious communities, and creating an attitude of mutual respect, respect, mutual assistance and affection despite religious differences. It is hoped that this research can provide recommendations for developing religious education curricula in schools as well as policies related to social harmony.